The Ontological Problem of Arkady Babchenko´s Cycle of Miniatures "Ten Series on the War" - Тетерина, Елена (Literatūra, 2017)
This article is devoted to the consideration of human ontological problems as the main genre sign of Arkady Babchenko’s cycle of miniatures Ten Series on the War. This prose of Babchenko is devoted to Russia’s Chechen Wars and realistically reproduces the modern realities.At the same time, its main meaning-making factor is the mythologeme of the Dante’s Purgatory. This generally introduces this text into the field of global literature’s reflection on the human destiny, his spiritual life and his main values. In Babchenko’s cycle, the image of the Purgatory has the semantics of a catastrophic space, in which, nevertheless, there is a chance for a spiritual rebirth of man. The process of building a war-maimed human soul is indicated by the symbolism of the Home, the Threshold and the Door. ARKADIJAUS BABČENKO MINIATIŪRŲ CIKLO „DEŠIMT SERIJŲ APIE KARĄ“ ONTOLOGINĖ PROBLEMATIKAStraipsnyje nagrinėjama Arkadijaus Babčenko miniatiūrų ciklo „Dešimt serijų apie karą“ ontologinė problematika kaip žanrinė dominantė. Šioje realistinėje Babčenko prozoje aprašomi Rusijos Federacijos karai Čečėnijoje ir vaizduojamos dabartinės realijos. Taip pat vienas iš prasmę kuriančių veiksnių cikle yra Dantės Skaistyklos mitologema, per kurią kūrinys patenka į pasaulinės literatūros kontekstą, kuriame apmąstoma žmogaus likimas, jo dvasinė būsena ir pagrindinės gyvenimo vertybės. Babčenko kūrinyje Skaistykla įgauna pražūtingos erdvės semantiką, tačiau šitoje erdvėje vis dar įmanomas dvasinis žmogaus atgimimas. Karo išdarkytos žmogaus sielos kūrimo procesas ženklinamas Namo, Slenksčio ir Durų simboliais.
Keywords: military prose; genre; miniature; mythology; Dante; Home; Рurgatory